Geoarchaeological Significance of a Younger Dryas Aged Black Mat, Tularosa Basin, Southern New Mexico. (2nd January 2016) - Rachal, David Michael; Taylor-Montoya, John; Goodwin, R. C.; Berryman, Stanley; Bowman, James
Abstract : Recent findings in the Tularosa Basin have revealed stratified deposits that contain a black mat that formed during the Younger Dryas (10, 900–9, 800 14 C yr BP). This black mat is in a sequence of buried geomorphic surfaces dating from 12, 300 to 9, 500 14 C yr BP, which together have a high probability of containing buried, intact Paleo-American remains. Continued research will yield important information about the peopling of the Americas and climate change during the late Pleistocene–Holocene transition.